Novel slide compression anatomic plates of the femoral neck for treating unstable femoral neck fracture: A biomechanical study. Issue 5 (29th September 2022) - Li, Jia; Yin, Pengbin; Li, Jiantao; Zhao, Zhe; Zhao, Jingxin; Cui, Xiang; Lyu, Houchen; Zhang, Licheng; Tang, Peifu
Abstract: To compare the biomechanical stability of slide compression anatomic plates of the femoral neck, cannulated compression screws and dynamic hip screws with derotation screws for stabilizing unstable femoral neck fractures (Pauwels angle = 70°). Pauwels III femoral neck fractures were created on 45 Sawbones femurs and randomly assigned to three implant groups (1:1:1). The biomechanical stability of all Sawbones in each treatment group was evaluated with three tests. First, in the static loading test, the load–displacement curve, vertical stiffness (load/vertical displacement [N/mm]) and 5 mm failure load were recorded. Second, in the incremental cyclic loading test (700, 1000, and 1400 N), the cyclic−displacement curve and the displacement of the fragments were recorded. Third, in the torsion test, the torsional rigidity, maximum torque, and torsional angle corresponding to the maximum torque were recorded. The static compression test showed that slide compression anatomic place‐femoral neck (SCAP‐FN) had the largest vertical stiffness (275 ± 11 N/mm, p < 0.01) and 5 mm failure load (1232 ± 156, p < 0.01). The cyclic loading test showed that SCAP‐FN had the lowest change in displacement after 30000 cycles of loading. The torsional stiffness and the maximum torque followed the order SCAP‐FN > dynamic hip screw systems (DHS) + derotational screw (DS) > CCS, and the torsional angle corresponding to the maximum torque followed the order SCAP‐FN < DHS + DS < CCS. The SCAP‐FN construct provides stiffness and stability compared with other standard fixation techniques (3CS and DHS + DS). The fixation strategy of SCAP‐FN might be sufficient for clinical use, indicating studies in the human body are warranted.